m6A-modification of cyclin D1 and c-myc IRESs in glioblastoma controls ITAF activity and resistance to mTOR inhibition - Benavides-Serrato, Angelica; Saunders, Jacquelyn T.; Kumar, Sunil; Holmes, Brent; Benavides, Kennedy E.; Bashir, Muhammad T.; Nishimura, Robert N.; Gera, Joseph (Cancer letters, 2023)
A major mechanism conferring resistance to mTOR inhibitors is activation of a salvage pathway stimulating internal ribosome entry site (IRES)-mediated mRNA translation, driving the synthesis of proteins promoting resistance of glioblastoma (GBM). Previously, we found this pathway is stimulated by the requisite IRES-trans-acting factor (ITAF) hnRNP A1, which itself is subject to phosphorylation and methylation events regulating cyclin D1 and c-myc IRES activity. Here we describe the requirement for m6A-modification of IRES RNAs for efficient translation and resistance to mTOR inhibition. DRACH-motifs within these IRES RNAs upon m6A modification resulted in enhanced IRES activity via increased hnRNP A1-binding following mTOR inhibitor exposure. Inhibitor exposure stimulated the expression of m6A-methylosome components resulting in increased activity in GBM. Silencing of METTL3-14 complexes reduced IRES activity upon inhibitor exposure and sensitized resistant GBM lines. YTHDF3 associates with m6A-modified cyclin D1 or c-myc IRESs, regulating IRES activity, and mTOR inhibitor sensitivity in vitro and in xenograft experiments. YTHDF3 interacted directly with hnRNP A1 and together stimulated hnRNP A1-dependent nucleic acid strand annealing activity. These data demonstrate that m6A-methylation of IRES RNAs regulate GBM responses to this class of inhibitors. •mTOR inhibitor resistance impedes their effective use for GBM management.•m6A modification of IRES-containing mRNAs promotes resistance to mTOR inhibition.•YTHDF3 and hnRNP A1 stimulate the translation of determinants crucial for resistance.•Cotargeting the m6A-methylosome and mTOR may be an effective anti-GBM strategy.